Pengaruh Murattal Alquran Terhadap Tingkat Stres Mahasiswa Muslim di Yogyakarta - Anisa Zahra Wijayanti Nugroho; Sri Kusrohmaniah (Faculty of Psychology, Universitas Gadjah Mada, 2019)
This study aimed to see the effect of the murattal Alquran on the level of individual stress. Hypothesis proposed in this research that there was influence of murattal Alquran in change of stress level experienced by experiment group and there was difference of stress levels between experiment and control group. The experimental design used was randomized pretest and posttest control group design. The subjects consisted of 45 participants age 18-22 years old, then divided into experiment group (n = 23) and control group (n = 22). The stress level was measured by stress subscale krom Depression, Anxiety, Stress Scale (DASS). Data were analyzed using ANOVA mixed method and the result showed the value of F = 10.386 (p < 0.05). That means, there was a significant change after listening to the Quranic murattal. The change in pretest and posttest score in the experimental group was shown with F = -5.957 (p < 0.05) and the control group had F = -1.136 (p > 0.05), meaning that there was a significant difference in the reduction of stress score of both groups . Moreover, the muratal Quran had an influence on changes in stress levels on the subject with an effective contribution of 19.4% (ETA2 = 0.194). Thus, the research hypothesis was accepted.